PENANGANAN KONFLIK MELALUI KEAMANAN DI KALIMANTAN BARAT INDONESIA - Elyta, Elyta (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2021)
Pontianak which is located in West Kalimantan, Indonesia, is considered as a conflict-prone area with 24 conflicts that happened until 2014. The purpose of this study is to determine and analyze how conflict is resolved in Pontianak. This research is qualitative research with data collection through direct observation and open interviews with key informants. Based on the results of the study, it is found that the prime reasons for conflict are boundaries dispute among the local communities, investment-plantation conflicts between the community and companies, political conflicts between local communities and the government. Regarding conflict management, the adoption of local wisdom values becomes the main important aspect in overcoming conflict. Through cooperation between the actors involved combined with the local value among the society, conflicts should be handled and it brings positive impact.